Modifications of Ribonucleases in Order to Enhance Cytotoxicity in Anticancer Therapy - Nassiri, Mohammadreza; Gopalan, Vinod; Vakili-Azghandi, Masoume (Current Cancer Drug Targets, 2022)
Ribonucleases (RNases) are a superfamily of enzymes that have been extensively studied since the 1960s. For a long time, this group of secretory enzymes was studied as an important model for protein chemistry such as folding, stability, and enzymatic catalysis. Since it was discovered that RNases displayed cytotoxic activity against several types of malignant cells, recent investigation has focused mainly on the biological functions and medical applications of engineered RNases. In this review, we describe the structures, functions, and mechanisms of antitumor activity of RNases. They operate at the crossroads of transcription and translation, preferentially degrading tRNA. As a result, this inhibits protein synthesis, induces apoptosis, and causes the death of cancer cells. This effect can be enhanced thousands of times when RNases are conjugated with monoclonal antibodies. Such combinations, called immunoRNases, have demonstrated selective antitumor activity against cancer cells both in vitro and in animal models. This review summarizes the current status of engineered RNases and immunoRNases as promising novel therapeutic agents for different types of cancer. Also, we describe our experimental results from published or previously unpublished research and compare them with other scientific information.
Keywords: immunoRNases